Practical musicology - Zagorski-Thomas, Simon (New York Bloomsbury Academic, 2022)
A theoretical framework for studying how music is made as opposed to what is produced"--
Introduction -- Context -- Musicking -- Learning and Knowing -- Communication and Influence -- Interaction and Influence -- Systems and Networks -- Afterword.
includes bibliographical references and index.
description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Musicology; Music -- Performance -- Research